Competing or complementary?: Socio-technical imaginaries of a bio-based construction sector - Lennart Fischer; Sebastian Losacker (TATuP – Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
The construction sector needs to transition toward using bio-based building materials in order to reduce its negative environmental impact. However, it is unclear how exactly such a bio-based future will look like, with different stakeholders in different geographical contexts having different visions of the sector’s future. Based on an extensive collection of expert interviews with stakeholders from the construction industry in China, India, Italy, and Germany, we have identified six primary visions. These are characterized by variations in their socio-technical logics, including preferred materials, targeted market segments, economic characteristics, and stage of development. While many visions appear to be complementary in principle, our findings also reveal conflicts, which are often socially constructed. These conflicts may impede the transition toward a bio-based construction sector, as certain visions may delegitimize alternative uses of bio-based materials.